Cheetahs - Nuzzolo, Deborah (Mankato, Minn. : Capstone Press, 2008)
Full-color photographs and simple text introduce young readers to the characteristics, behaviors, and habitats of cheetahs.
Wilson's Children, July 2009
Horn Book, October 2008
Library Media Connection, August 2008
Includes bibliographical references (p. 23) and index.
1.5
K-3
Keywords: Cheetah -- Africa -- Juvenile literature; Cheetah; Cheetahs